Peran Kepuasan dan Loyalitas Pelanggan terhadap Niat Pembelian Ulang dengan Customer Relationship Management sebagai Variabel Mediasi - Nabila Alzari (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The rapid expansion of e-commerce in Indonesia has reshaped consumer habits and heightened competition among digital marketplaces. This research seeks to examine how customer satisfaction and loyalty influence repurchase intention, with Customer Relationship Management (CRM) serving as an intermediary variable. A quantitative approach was adopted through a survey method involving 340 Indonesian e-commerce consumers. Data were gathered via an online questionnaire and analyzed using regression and path analysis with the SPSS program. The findings indicate that customer satisfaction and loyalty both exert a positive and significant effect on consumers’ intention to repurchase. Additionally, CRM functions as a partial mediator that strengthens the connection between satisfaction, loyalty, and repurchase intention. These results align with consumer behavior theory, suggesting that favorable experiences and emotional connections drive repeated purchase decisions. The study highlights that CRM should be viewed not only as an operational mechanism but as a strategic approach to fostering customer retention and sustaining long-term competitiveness in the digital business environment. Practically, it recommends the implementation of data-driven CRM systems that support personalized communication, real-time engagement, and loyalty-based initiatives to enhance customer experiences and encourage consistent repurchase behavior.